Women: the key to food security - Quisumbing, Agnes R.; Brown, Lynn R.; Feldstein, Hilary Sims; Haddad, Lawrence J.; Peña, Christine (International Food Policy Research Institute, 2000)
This brief examines the key roles that women play in ensuring food security and makes three recommendations of ways to strengthen the food security through policies and programs that enhance women's abilities and resources to fulfill their roles.